The SCN Clock Governs Circadian Transcription Rhythms in Murine Epididymal White Adipose Tissue. (December 2016) - Kolbe, Isa; Husse, Jana; Salinas, Gabriela; Lingner, Thomas; Astiz, Mariana; Oster, Henrik
The circadian master pacemaker in the suprachiasmatic nucleus (SCN) orchestrates peripheral clocks in various organs and synchronizes them with external time, including those in adipose tissue, which displays circadian oscillations in various metabolic and endocrine outputs. Because our knowledge about the instructive role of the SCN clock on peripheral tissue function is based mainly on SCN lesion studies, we here used an alternative strategy employing the Cre/ loxP system to functionally delete the SCN clock in mice. We performed whole-genome microarray hybridizations of murine epididymal white adipose tissue (eWAT) RNA preparations to characterize the role of the SCN clock in eWAT circadian transcriptome regulation. Most of the rhythmic transcripts in control animals were not rhythmic in SCN mutants, but a significant number of transcripts were rhythmic only in mutant eWAT. Core clock genes were rhythmic in both groups, but as was reported before for other tissues, rhythms were dampened and phase advanced in mutant animals. In SCN-mutant mice, eWAT lost the rhythm of metabolic pathway–related transcripts, while transcripts gaining rhythms in SCN-mutant mice were associated with various immune functions. These data reveal a complex interaction of SCN-derived and local circadian signals in the regulation of adipose transcriptome programs.